A Brief Overview on Surveillance Methods for the Rare Health Events - Sasikumar Ramaraj; Bangusha Devi Subramanian (Current Overview on Disease and Health Research Vol. 2, 2022)
There is a problem for monitoring the incidence rate of an event of interest where the baseline probability of the event is small arises in industrial, medical and other fields. There are only few statistical methods for use in formal approaches to the problem of the investigation of rare health events. The CUSUM method, which was used to spot tiny shifts in the process, is the foundation of the most well-known surveillance procedures, with the exception of the first quality control chart introduced by Shewhart. However, this graph fails to show a rise in rate when the event’s baseline probability is extremely low. Some of the other methods were developed to carry out this problem like Sets method, CUSCORE (Cumulative Score) method and CUSUM (Cumulative Sum) method based on Bernoulli distribution. A detailed review of these three methods in the field of health science discussed with the help of earlier literatures and also the role of essential of these methods in the same field are discussed.